Prenatal sonographic diagnosis of tetralogy of fallot - Tongsong T. (2014)
The objective of this report was to emphasize the sonographic findings of tetralogy of Fallot (TOF) during the prenatal period. Four fetuses with TOF were prenatally diagnosed at gestational ages of 25, 28, 25, and 32 weeks. Based on this small series, prenatal sonographic findings suggestive of TOF may be summarized as follows: (1) a large aortic root, which is the most common prenatal sonographic finding, (2) a small pulmonary artery or stenosis of the right ventricular outflow tract, (3) a ventricular septal defect in the outlet portion of the septum, (4) an overriding aorta, which is best seen in the long-axis view, and (5) right ventricular hypertrophy. Other findings such as hydrops fetalis or polyhydramnios may also be helpful especially in the case of dysplastic pulmonary valves. The demonstration of a normal aortic root would render the presence of TOF unlikely. TOF with pulmonary atresia can be confused with truncus arteriosus, in which both pulmonary arteries arise from the ascending aorta. However, with careful examination along the course of the ascending aorta, there are no branches arising from the aorta in TOF. © 2005 Wiley Periodicals, Inc.